The expositor's Bible commentary - Zondervan Interactive (Firm) (Grand Rapids, Mich. : Zondervan Interactive, 1998)
Electronic version of the twelve-volume printed work by the same title. Features introductions and outlines for each book of the Bible, commentaries by seventy-eight biblical scholars, complete text of New International version of the Bible, original Greek text, and Aramaic, Greek, and Hebrew transliterations.
Title from disc label.
System requirements: IBM-compatible 386 PC; Windows 3.1 or 95; 5MB hard disk space; Windows-supported video card; CD-ROM drive.
In English, Aramaic, Greek, and Hebrew.
Keywords: Bible -- Commentaries